PARTISIPASI MASYARAKAT DALAM MEWUJUDKAN KAMPUNG WISATA UNGGULAN DI SUNGAI MEMPURA KABUPATEN SIAK - Nurul Khomariah; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The Mempura River Tourism Village is a tourist village located in Siak Regency. This tourist village has quite good natural potential and is still beautiful, and cultural arts are still very awake. This study aims to determine community participation in developing the Mempura River Tourism Village and to find out the barriers to community participation in developing the Mempura River Tourism Village.This study uses a qualitative method with a descriptive approach. The research subjects were the Tourism Office of Siak Regency, the tourism conscious group (pokdarwis) of Mempura River, the Mempura River community and the chairman of the Malay traditional institution. Data collection is done through observation, document study, interviews and documentation. While data analysis is done by reducing data, presenting data, drawing conclusions. The results of this study indicate that the Mempura River Tourism Village has natural attractions such as the beauty of the river, agro-tourism such as durian gardens, cultural arts such as silat, zapin and kompang which are still maintained. However, community participation in the Mempura River Tourism Village is still low in advancing their villages. Accessibility to the Mempura River Tourism Village is very easy with good road conditions. Keywords : Community Participation, Tourist Village, the Mempura River